Answer:
Step-by-step explanation:
We'll take this step by step. The equation is
![8-3\sqrt[5]{x^3}=-7](https://tex.z-dn.net/?f=8-3%5Csqrt%5B5%5D%7Bx%5E3%7D%3D-7)
Looks like a hard mess to solve but it's actually quite simple, just do one thing at a time. First thing is to subtract 8 from both sides:
![-3\sqrt[5]{x^3}=-15](https://tex.z-dn.net/?f=-3%5Csqrt%5B5%5D%7Bx%5E3%7D%3D-15)
The goal is to isolate the term with the x in it, so that means that the -3 has to go. Divide it away on both sides:
![\sqrt[5]{x^3}=5](https://tex.z-dn.net/?f=%5Csqrt%5B5%5D%7Bx%5E3%7D%3D5)
Let's rewrite that radical into exponential form:
![x^{\frac{3}{5}}=5](https://tex.z-dn.net/?f=x%5E%7B%5Cfrac%7B3%7D%7B5%7D%7D%3D5)
If we are going to solve for x, we need to multiply both sides by the reciprocal of the power:
![(x^{\frac{3}{5}})^{\frac{5}{3}}=5^{\frac{5}{3}}](https://tex.z-dn.net/?f=%28x%5E%7B%5Cfrac%7B3%7D%7B5%7D%7D%29%5E%7B%5Cfrac%7B5%7D%7B3%7D%7D%3D5%5E%7B%5Cfrac%7B5%7D%7B3%7D%7D)
On the left, multiplying the rational exponent by its reciprocal gets rid of the power completely. On the right, let's rewrite that back in radical form to solve it easier:
![x=\sqrt[3]{5^5}](https://tex.z-dn.net/?f=x%3D%5Csqrt%5B3%5D%7B5%5E5%7D)
Let's group that radicad into groups of 3's now to make the simplifying easier:
because the cubed root of 5 cubed is just 5, so we can pull it out, leaving us with:
which is the same as:
![x=5\sqrt[3]{25}](https://tex.z-dn.net/?f=x%3D5%5Csqrt%5B3%5D%7B25%7D)
Answer:
Somewhere around 6 or 9
Step-by-step explanation:
Answer:
f(x) = 4x² - 1
Step-by-step explanation:
The given function is; f(x) = x²
Now, when stretched vertically by a factor of 4, we have;
f(x) = 4x²
It's now shifted 1 unit down.. Thus, the final function will be;
f(x) = 4x² - 1
answer: x > - 1.25
Step-by-step explanation:
0.2 •(x + 20)- 3> -7- 6.2x
0.2x + 1> - 7 - 6.2x
Answer:
12
Step-by-step explanation:
21=31
31=7+2-3+0=12
This is correct because linear equations mean add subtract divide and multiply instead of finding roots and squares